The Participation Level of The Local Community towards Community-Based Tourism Development in Sopapei Tourism Destination, Ambon, Indonesia - Wawo, Mintje; Tetelepta, Johannes M.S.; Willem Ayal, Frederik; A.B Mamesah, Juliaeta; Rahman; Bernard Hehakaya, Trealy (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Community-based tourism is owned and managed by the community and intended to deliver wider community livelihood benefits. Sopapei Beach is one of the tourist destination spots in Ambon, and it is visited mostly by local tourists. This area has six tourism spots, all managed by individual local communities. This study aimed to investigate the potency of developing community-based tourism in this area. The study was conducted between July – September 2023. Descriptive statistical analysis was used in this study. An interview, field observation, and literature review were used to obtain information on tourism activity and mechanisms in Sopapei Beach. A purposive sampling method was used to collect the informant to be interviewed. The SWOT analysis was used to develop strategy management for community-based tourism (CBT) development possibilities. The result shows that most informants claim that Sopapei is an attractive tourist spot with a fascinating marine view, a friendly atmosphere, a nice beach, and attractive culinary dishes. There was a small probability of conflict potency between the local tourism owners. The CBT management approach was a possibility to reduce the conflict potency. Participatory of the local community in the local community in tourism was considered fair. SWOT analysis proposes 13 management strategies for developing CBT in Sopapei Beach.